Factors influencing prescription and administration of analgesic medication: A longitudinal study of people with dementia living in care homes. (14th March 2021) - La Frenais, Francesca; Vickerstaff, Victoria; Cooper, Claudia; Livingston, Gill; Stone, Patrick; Sampson, Elizabeth L.
Abstract: Objectives: To (1) describe the prescription and administration of regular and 'as required' (pro re nata [PRN]) analgesics in English care homes, (2) investigate individual and care home factors associated with analgesic use. Methods: We collected data (2014–2016) at 0‐, 4‐, and 12‐months nested in a longitudinal cohort study of 86 English care homes about residents with diagnosed or probable dementia. We describe analgesics prescribed as regular or PRN medication, by class, and PRN administration. We explored individual differences (sociodemographic; dementia severity [Clinical Dementia Rating]), and care home differences (type; ownership; number of beds; dementia‐registered/specialist; Care Quality Commission rating) in prescription and administration using multilevel regression models. Results: Data were available for 1483 residents. At baseline, 967 residents (67.9%) were prescribed analgesics: 426 residents (28.7%) prescribed regular analgesics and 670 (45.2%) prescribed PRN. Paracetamol was the most prescribed analgesic (56.7%), with PRN prescriptions more common than regular (39.7% vs. 16.6%). Across all study visits, 344 residents (mean = 41.9%) with a PRN prescription did not receive any analgesic in the 2 weeks prior to data collection. Male residents and those with severe dementia received fewer analgesics. Care homes differences in PRN administration were not explained by the modelled variables. Conclusions: Pain management in English care homes largely relies on PRN paracetamol that is frequently prescribed but infrequently administered. Care homes differ in how often they administer PRN analgesics. Some care home residents particularly those with more severe dementia are likely to have untreated pain. Key points: English care home residents with dementia are frequently prescribed pro re nata (PRN) analgesics but these are infrequently administered. Some groups of residents (male, more severe dementia) receive fewer analgesics and may be at risk of undertreatment for pain. Before prescribing pain relief, clinicians need to consider the risk that PRN analgesics may not be administered. Pragmatic pain management guidelines specifically for care home residents with dementia and improving medication documentation may optimise analgesic use.